Muhafidhah Novie* dan Edi Rustia PENGARUH MOTIVASI DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA PADA PENYANDANG HIV DIYAYASAN DELTA CRISIS CENTER SIDOARJO : Program Studi Manajemen, Universitas Nahdlatul Ulama Sidoarjo *e-mail: muhafidhahnovie.unusida@gmail.com - Muhafidhah Novie* dan Edi Rustiawan (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Penelitian This study aims to determine the effect of family motivation and environment on the interest in entrepreneurship in people with HIV in the Sidoarjo Delta Crisis Center. The analysis tool used is SPSS. This study uses multiple linear regression analysis with 30 respondents. The results of data processing obtained the value of beta X1 (motivation) of 0.455 with the value of sig. equal to 0,000 or 0%. Sig value 0,000 <0,05 shows that motivation has a significant positive effect on interest in entrepreneurship and the regression results obtained beta X2 (family environment) of 0,233 with a sig value. amounting to 0.048 or 0.4%. Sig value 0.048 <0.05 indicates that the family environment has a significant positive effect on the interest in entrepreneurship. These results indicate that motivation and family environment are very influential simultaneously on the interests of entrepreneurship. Partially the motivation and family environment have a positive effect on the interest in entrepreneurship.